2017
DOI: 10.1001/jamacardio.2017.0022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemic Postconditioning During Primary Percutaneous Coronary Intervention for Patients With ST-Segment Elevation Myocardial Infarction

Abstract: clinicaltrials.gov Identifier: NCT01435408.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 38 publications
3
88
0
1
Order By: Relevance
“…These results correspond to data published by Hahn et al from a multicenter study of 700 patients (POST [Effects of Postconditioning On Myocardial Reperfusion] trial, https://clinicaltrials.gov/show/NCT00942500) that was conducted between 2009 and 2012, also showing no cardiprotective effect 10. Moreover, recently published results of the DANAMI‐3–iPOST (DANish Study of Optimal Acute Treatment of Patients With ST‐elevation Myocardial Infarction, https://clinicaltrials.gov/show/NCT01435408) trial have also demonstrated that IPoC in addition to primary percutaneous coronary intervention failed to significantly reduce death from any cause or hospitalization during a median follow‐up of 38 months 11…”
Section: Introductionmentioning
confidence: 99%
“…These results correspond to data published by Hahn et al from a multicenter study of 700 patients (POST [Effects of Postconditioning On Myocardial Reperfusion] trial, https://clinicaltrials.gov/show/NCT00942500) that was conducted between 2009 and 2012, also showing no cardiprotective effect 10. Moreover, recently published results of the DANAMI‐3–iPOST (DANish Study of Optimal Acute Treatment of Patients With ST‐elevation Myocardial Infarction, https://clinicaltrials.gov/show/NCT01435408) trial have also demonstrated that IPoC in addition to primary percutaneous coronary intervention failed to significantly reduce death from any cause or hospitalization during a median follow‐up of 38 months 11…”
Section: Introductionmentioning
confidence: 99%
“…However, other investigators have reported no benefit [11][12][13] or even increasing of the ischemic damage [14,15]. It is worth noting that in the induction of IPostC the number of cycles and their duration varied and none of the studies examined the importance of the duration of the reoxygenation interval between the ischemic insult and IPostC application.…”
Section: Discussionmentioning
confidence: 99%
“…These findings do not support a wide clinical application of IPostC until the most effective protocol is fully defined in clinical settings and the patients that can be benefit from the treatment are identified. This approach is justified by the results recently published of the DANAMI-3-iPOST clinical trial [13] in which routine IPostC during primary angioplasty failed to reduce a composite outcome of death and hospitalization for heart failure in 1234 patients with an acute myocardial infarction. It is clear that further laboratory research will be required for a better understand of the mechanism of protection by IPostC that would help to refine the much needed interventions of effective therapies at the time of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models of myocardial infarction, IPoC resulted in improved myocardial metabolic recovery and increased myocardial salvage . However, in contrast to the beneficial effects observed in animal models, IPoC studies in human using surrogate markers of myocardial salvage yielded to conflicting results . In the recent Third Danish Study of Optimal Acute Treatment of Patients With ST‐Elevation Myocardial Infarction–Ischemic Postconditioning (DANAMI‐3‐iPOST), the largest IPoC trial in STEMI to date ( N = 1,234 randomized patients), routine IPoC (performed after restoration of coronary flow with multiple cycles of balloon inflation and deflation and prior to final stent deployment) failed to reduce the composite endpoint of all‐cause death or hospitalization for heart failure at a median follow‐up time of ≈3 years .…”
mentioning
confidence: 99%